10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BACKGROUND: Patient-reported outcome measures (PROMs) are relevant in sleep medicine, but CPAP-specific PROMs for obstructive sleep apnea (OSA) remain insufficiently characterized. We hypothesized that a PROM tailored to CPAP initiation would show acceptable psychometric performance, capture perceived benefit and treatment burden, and identify clinically relevant differences in subject experience to inform adherence support. METHODS: We conducted a prospective cohort study from April 2023 to December 2024 at the Pulmonology Service, with a home respiratory care provider. PROM development included item generation and reduction, qualitative/cognitive validation with test-retest assessment, and large-scale digital administration in routine care. The instrument assessed 3 domains activity/daytime sleepiness, psychophysical status, and treatment tolerance. Internal consistency was evaluated with Cronbach alpha and reproducibility with intraclass correlation coefficients (ICC). Continuous and categorical variables were analyzed with parametric or nonparametric tests. RESULTS: The qualitative validation phase included 20 subjects (16 men, 4 women; 69 ± 9 y), and the clinical application phase included 985 subjects (757 men, 228 women; 64 ± 11 y). Cronbach alpha was 0.792 for activity/daytime sleepiness, 0.835 for psychophysical aspects, 0.906 for total benefit, and 0.69 for treatment tolerance. ICC values were 0.963, 0.976, 0.99, and 0.949, respectively. Mean total benefit was 29 ± 8/40, with 75% scoring >24. Mean tolerance was 8.5 ± 3/30, with 98.6% scoring <18. Favorable responses were reported for reduced fatigue (83%), greater daytime activity (75%), less daytime sleepiness (84%), better disease control (96%), safer driving (75%), improved mood (75%), energy (80%), and improved concentration (74%). Men reported greater benefit, whereas women reported more claustrophobia, skin marks, and hair-related inconvenience. CONCLUSIONS: This CPAP-specific PROM showed good internal consistency, reproducibility, and practical clinical utility, identifying benefit/good tolerance and subgroups needing personalized follow-up and adherence support.